2010
DOI: 10.1038/nature08897
|View full text |Cite
|
Sign up to set email alerts
|

Learning-related fine-scale specificity imaged in motor cortex circuits of behaving mice

Abstract: Cortical neurons form specific circuits, but the functional structure of this microarchitecture and its relation to behaviour are poorly understood. Two-photon calcium imaging can monitor activity of spatially defined neuronal ensembles in the mammalian cortex. Here we applied this technique to the motor cortex of mice performing a choice behaviour. Head-fixed mice were trained to lick in response to one of two odours, and to withhold licking for the other odour. Mice routinely showed significant learning with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
406
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 434 publications
(441 citation statements)
references
References 37 publications
32
406
3
Order By: Relevance
“…The nature of these fluctuations seems similar to fluctuations in the BOLD fMRI signal in nonhuman (25) and human (26) primates and in the IOS and Doppler signals from rodents (24). Thus, the transcrianal imaging technique we used may be of use to explore the mechanistic basis of these ubiquitous oscillations (27) in behaving mice (28,29).…”
Section: Discussionmentioning
confidence: 87%
“…The nature of these fluctuations seems similar to fluctuations in the BOLD fMRI signal in nonhuman (25) and human (26) primates and in the IOS and Doppler signals from rodents (24). Thus, the transcrianal imaging technique we used may be of use to explore the mechanistic basis of these ubiquitous oscillations (27) in behaving mice (28,29).…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, future research will have to tackle network functions at the level of ensembles of individual identified synapses and neurons in vivo. Further progress will probably depend on the development of methods to image synapses and their molecular components with high sensitivity and spatiotemporal resolution in situ [109][110][111] . Exciting recent developments mainly, but not exclusively, based on calcium imaging have achieved sufficient resolution to monitor function at the level of ensembles of spines in the neocortex 112,113 .…”
Section: Microcircuitmentioning
confidence: 99%
“…In a typical experiment, an area of the skull is surgically removed and replaced with a cover glass to provide optical access to the underlying structure of interest (4). For imaging during behavior, the cover glass is often attached to an optically transparent plug embedded in the skull to improve mechanical stability and to prevent the skull from growing back and blocking the optical access (5,6) (Fig. 1A).…”
mentioning
confidence: 99%